2019
DOI: 10.1021/acsami.9b14345
|View full text |Cite
|
Sign up to set email alerts
|

Adhesive-Layer-Free and Double-Faced Nanotransfer Lithography for a Flexible Large-Area MetaSurface Hologram

Abstract: Herein, we develop an adhesive-free double-faced nanotransfer lithography (ADNT) technique based on the surface deformation of flexible substrates under the conditions of temperature and pressure control and thus address the challenge of realizing the mass production of large-area nanodevices in the fields of optics, metasurfaces, and holograms. During ADNT, which is conducted on a flexible polymer substrate above its glass transition temperature in the absence of adhesive materials and chemical bonding agents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 47 publications
(58 reference statements)
1
24
0
Order By: Relevance
“…However, it was reduced to 14% under 3 bar of pressure. Therefore, we can conclude that the pressure, heating time, and heating temperature have significant effects on the controllability of the nanogaps; this phenomenon is consistent with the results of previous studies , (when heated above their T g, PMMA resin and films deform depending on the applied pressure, heating temperature, and heating time). In addition, the detail experimental conditions of the fabricated nanogaps are provided in Table S1.…”
Section: Resultssupporting
confidence: 92%
“…However, it was reduced to 14% under 3 bar of pressure. Therefore, we can conclude that the pressure, heating time, and heating temperature have significant effects on the controllability of the nanogaps; this phenomenon is consistent with the results of previous studies , (when heated above their T g, PMMA resin and films deform depending on the applied pressure, heating temperature, and heating time). In addition, the detail experimental conditions of the fabricated nanogaps are provided in Table S1.…”
Section: Resultssupporting
confidence: 92%
“…Heterogeneous nanostructures, unique nanoarchitecture with bi- or multimetallic construction, have gained considerable attention in the development of catalysts, , sensors, transistors, nanogenerators, photovoltaic devices, batteries, metasurfaces, , and plasmonic structures. , In these devices, the core elements with unprecedented performance are nano-manufactured functional materials, such as nanoparticles, nanorods, nanowires, nanopillars, nanoboxes, and nanoribbons, whose physical properties and functions are fundamentally different from those of the bulk materials. , In particular, the combination of unique nanostructures and multiple noble metal construction provides enhanced catalytic properties and optical properties. For example, several studies have reported reliable and sensitive gas sensors based on heterogeneous nanowires with various noble-metal (e.g., Ag, Au) catalysts. Additionally, various other noble metal-based heterogeneous nanostructures with ultra-small nanogaps (including nanoparticles, nanopillars, nanoboxes) have been extensively fabricated.…”
Section: Introductionmentioning
confidence: 99%
“…Heterogeneous nanostructures, unique nanoarchitecture with bi-or multimetallic construction, have gained considerable attention in the development of catalysts, 1,2 sensors, 3−5 transistors, 6 nanogenerators, 7 photovoltaic devices, 8 batteries, 9 metasurfaces, 10,11 and plasmonic structures. 12,13 In these devices, the core elements with unprecedented performance are nano-manufactured functional materials, such as nanoparticles, nanorods, nanowires, nanopillars, nanoboxes, and nanoribbons, whose physical properties and functions are fundamentally different from those of the bulk materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In addition, multilayer stacks can offer new emergent properties by taking advantage of the behavior of collective materials, which would have broad impact on catalysis, energy, medicine, and optics. The complicated and costly lithographic fabrication techniques and other direct-write techniques allow for nanofabricating layered structures with precise component registry and alignment. However, these top-down fabrication techniques are time-consuming, limited to small areas, and not readily amenable for the dynamic, tunable, or soft materials required for many applications. , Building nanostructures from bottom-up fabrication techniques, such as layer-by-layer (LbL) deposition, utilizing self-assembly approach techniques has enabled high nanoscale precision fabrication at a massively parallel scale with low cost.…”
Section: Introductionmentioning
confidence: 99%